EFFECT OF STORAGE CHANGES ON COMPLETE BLOOD COUNT PARAMETERS IN RELATION TO TIME AND TEMPERATURE (The Research of Medical Science Review, 2025)
Background: The stability of complete blood count (CBC) parameters over time and under different storage conditions is crucial for ensuring accurate diagnostic results. This study investigates the effect of storage at room temperature (22°C) and refrigeration (4°C) on CBC parameters over a 24-hour period. Objective: To evaluate the impact of storage temperature and time on CBC parameters, including hemoglobin (Hb), red blood cell count (RBC), mean cell volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW), white blood cell count (WBC), and platelet count. Methods: A descriptive cross-ectional study was conducted at the Department of Pathology, Hematology Section, Fatima Jinnah Medical University, Lahore. A total of 100 CBC blood samples, collected in K2 EDTA vials, were analyzed using the Sysmex XP 300 hematology analyzer immediately after collection (fresh sample) and after 24 hours of storage at room temperature (22°C) and 4°C. Results: A total of 100 patients were added in the study, with a mean age of 35.6 ± 12.4 years. The age distribution showed that 40% of participants were between 18-30 years, 35% were between 31-45 years, 15% were between 46-60 years, and 10% were over 60 years. Most participants (85%) were healthy, while 7% had hypertension, 5% were diabetic, and 3% had other conditions such as hyperlipidemia. Hemoglobin (Hb) showed a slight decrease at room temperature (14.2 ± 1.3) compared to the fresh sample (14.5 ± 1.2), but remained stable at 4°C (14.4 ± 1.1). RBC Count had a p- value of 0.73, WBC Count had a p-value of 0.82, and Platelet Count showed a p-value of 0.91, all of which are above the 0.05 threshold for significance. Conclusion: It is concluded that storage of blood samples at 4°C for up to 24 hours preserves the integrity of CBC parameters, while storage at room temperature may lead to minor alterations. Refrigeration at 4°C is recommended for the preservation of CBC values, and blood samples should be processed promptly to ensure accuracy in clinical diagnostics.